2020
DOI: 10.1002/app.49068
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced CO2 selectivity of polyimide membranes through dispersion of polyethyleneimine decorated UiO‐66 particles

Abstract: Branched polyethyleneimine (PEI) functionalized UiO‐66 were synthesized and used as fillers to fabricated mixed‐matrix membranes (MMMs) for CO2/CH4 separation. The purpose of introducing amino‐functional groups in the filler is to improve the interfacial compatibility of the filler with the polymer through the formation of hydrogen bonds with the carbonyl group of 6FDA‐ODA. Additionally, the amino group can facilitate CO2 transport through a reversible reaction, enhancing the CO2/CH4 separation properties of M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(8 citation statements)
references
References 66 publications
2
2
0
Order By: Relevance
“…On another work, Ahmad et al evidenced that the ligand functionalization of UiO-66­(Zr) by NH-COCH 3 groups only slightly increases the CO 2 /CH 4 selectivity of the corresponding UiO-66-NH-COCH 3 /6FDA-DAM MMM as compared with its pristine UiO-66­(Zr) analogue (33 vs 31) again associated with a decrease of the CO 2 permeability (1263 barrer vs 1912 barrer). A similar permeability/selectivity trade-off was reported by Liu et al for a polyethyleneimine functionalized UiO-66/6FDA-ODA MMM. More recently, Knebel et al successfully enhanced both propylene permeability and propylene/propane selectivity of a ZIF-67/6FDA-DAM MMM by functionalizing the MOF with the 1,3-bis­(2,4,6-diisopropylphenyl)­imidazole-2-ylidene (iDip) function.…”
Section: Introductionsupporting
confidence: 84%
See 1 more Smart Citation
“…On another work, Ahmad et al evidenced that the ligand functionalization of UiO-66­(Zr) by NH-COCH 3 groups only slightly increases the CO 2 /CH 4 selectivity of the corresponding UiO-66-NH-COCH 3 /6FDA-DAM MMM as compared with its pristine UiO-66­(Zr) analogue (33 vs 31) again associated with a decrease of the CO 2 permeability (1263 barrer vs 1912 barrer). A similar permeability/selectivity trade-off was reported by Liu et al for a polyethyleneimine functionalized UiO-66/6FDA-ODA MMM. More recently, Knebel et al successfully enhanced both propylene permeability and propylene/propane selectivity of a ZIF-67/6FDA-DAM MMM by functionalizing the MOF with the 1,3-bis­(2,4,6-diisopropylphenyl)­imidazole-2-ylidene (iDip) function.…”
Section: Introductionsupporting
confidence: 84%
“…22 On another work, Ahmad et al 27 evidenced that the ligand functionalization of UiO-66(Zr) by NH-COCH 3 groups only slightly increases the CO 2 /CH 4 selectivity of the corresponding UiO-66-NH-COCH 3 /6FDA-DAM MMM as compared with its pristine UiO-66(Zr) analogue (33 vs 31) again associated with a decrease of the CO 2 permeability (1263 barrer vs 1912 barrer). A similar permeability/selectivity tradeoff was reported by Liu et al 29 From the polymer functionalization side, Carja et al 21 revealed that while PIM-1 functionalized with amidoxime ensures an improvement of the adhesion with UiO-66 in the corresponding MMM, it also induces a significant drop of gas permeability compared with the UiO-66/PIM-1 analogue. Tien-Binh et al 20 demonstrated that functionalizing both MOF (MIL-53 with −NH 2 groups) and polymer (6FDA-DAM-HAB with −OH functions) components leads to an increase of the CO 2 /CH 4 selectivity from 2.2 to 5.1 for the resulting MMM while maintaining comparable CO 2 permeability.…”
Section: Introductionsupporting
confidence: 74%
“…Schematic representation of UiO-66 modification routes by polymer decoration through a) covalently bonded with UiO-66 linker, NH 2 –BDC, from ref and b) covalently bonded with UiO-66 metals, open coordination sites, from ref .…”
Section: Mof-based Mmms For Co2 Separationmentioning
confidence: 99%
“…Therefore, PEI has often been used to modify porous materials to improve the adsorption performance of materials for CO 2 . 4,4 -(hexafluoroisopropylidene) diphthalic anhydride-4,4 -diphenylamine (6FDA-ODA) was selected as the polymer matrix to successfully prepare a mixed-matrix membrane loaded with UIO-66-PEI particles with high separation efficiency [63]. PDMS is also a polymer commonly used in gas separation membranes, but when used with MOF particles, it causes pore blockage, thus reducing membrane permeability.…”
Section: University Of Oslomentioning
confidence: 99%